Ensuring Security in the Age of Intelligent Connectivity: Strategic Insights for 6G Networks - Roberts, Charlotte; Yerram, Sridhar Reddy (Engineering International, 2023)
The emergence of intelligent connection and 6G networks promises opportunities for advancement and creativity but poses serious cybersecurity risks. This paper offers tactical perspectives on protecting 6G networks in the face of intelligent connectivity's intricacies. The primary goals are to recognize new threats, evaluate strategic approaches to cyber resilience, investigate security solution innovations, and look at global cooperation and regulatory frameworks. The study's methodology involves synthesizing existing literature and scholarly works through secondary data analysis. Key conclusions highlight the changing nature of the threat landscape, the significance of cyber resilience, innovation's role in security solutions, and the need for robust regulatory frameworks and international cooperation. The consequences of policy highlight the necessity of adaptable regulatory frameworks, resource allocation for cybersecurity, and ongoing threat landscape modification. This research provides insightful information to help stakeholders in academia, business, and government negotiate the difficulties of maintaining security in the era of intelligent connection and 6G networks.
Keywords: Security; Intelligent Connectivity; 6G Networks; Cybersecurity; Network Protection; Data Privacy; Threat Mitigation